DEIXIS USE IN “AL-QALB AL-JARȊH” SHORT STORY BY NAJIB KAILANI (A PRAGMATIC STUDY) - Sammad Hasibuan (Arabic Literature Department, 2021)
This study describe the types of deixis and their functions contained in the short story al-Qalb al-Jarȋh by Najib Kailani. Through deixis, readers or listeners will be helped to know who, when, and where an utterance is carried out based on its context. In this study, the method used is descriptive-qualitative with a pragmatic approach. The object of the research is the short story al-Qalb al-Jarȋh, while the research data in the form of words, phrases, and sentences identified contain elements of deixis. The results of the study prove that the short story of al-Qalb al-Jarȋh by Najib Kailani contains various elements of deixis, including: person deixis, time deixis, place deixis, discourse deixis, and social deixis.